Effect of plane of nutrition in early life on the transcriptome of visceral adipose tissue in Angus heifer calves - Keogh, Kate (Sci Rep, 2021)
Adipose tissue represents not only an important energy storage tissue but also a major endocrine organ within the body, influencing many biochemical systems including metabolic status, immune function and energy homeostasis. The objective of this study was to evaluate the effect of an enhanced dietary intake during the early calfhood period on the transcriptome of visceral adipose tissue. Artificially reared Angus × Holstein–Friesian heifer calves were offered either a high (HI, n = 15) or moderate (MOD, n = 15) plane of nutrition from 3 to 21 weeks of life. At 21 weeks of age all calves were euthanized, visceral adipose harvested and samples subsequently subjected to mRNA sequencing. Plane of nutrition resulted in the differential expression of 1214 genes within visceral adipose tissue (adj. p < 0.05; fold change > 1.5). Differentially expressed genes were involved in processes related to metabolism and energy production. Biochemical pathways including Sirtuin signalling (adj. p < 0.0001) and the adipogenesis pathways (adj. p = 0.009) were also significantly enriched, indicating greater metabolic processing and adipogenesis in the calves on the high plane of nutrition. Results from this study identify novel genes regulating the molecular response of visceral adipose tissue to an improved plane of nutrition during early calfhood.